Semi-flexible pavement height difference repairing material as well as preparation method and application thereof
By using semi-flexible pavement height difference repair materials, combined with cement-based dry powder mortar and modified emulsified asphalt, the shortcomings of existing materials in construction convenience, adhesion and durability are solved, and efficient and safe pavement repair results are achieved.
Patent Information
- Application Number
- CN202411861214.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-17
- Publication Date
- 2025-04-29
- Estimated Expiration
- 2044-12-17
AI Technical Summary
The existing pavement height difference repair materials have shortcomings in construction convenience, adhesion to the original pavement, water damage resistance and durability, and it is difficult to effectively solve the pavement height difference problem, affecting driving safety and road life.
A semi-flexible pavement height difference repair material is used, which consists of cement-based dry powder mortar and SBR-SiO2 composite modified emulsified asphalt mixture, aggregate and water. Through the combination of modified emulsified asphalt and nanomaterials, the compatibility and durability of the material are improved.
It realizes convenient construction, good bonding performance, strong compressive strength and volume stability of the road surface height difference repair materials, improves the rut resistance and durability of the road surface, and ensures driving comfort and safety.
Smart Images

Figure BDA0005193246330000131 
Figure BDA0005193246330000141 
Figure BDA0005193246330000181
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of pavement materials, and in particular to a semi-flexible pavement height difference repair material and a preparation method and application thereof. Background Art
[0002] In recent years, my country's expressways have developed rapidly, and roads have gradually shifted from construction-oriented to maintenance-oriented. In road maintenance, local height differences in asphalt pavements appear at locations such as bridge expansion joints, expressway climbing sections, around cellar covers, and uneven settlement of bridge heads. The appearance of height differences can cause vehicles to bounce and impact when passing, affecting driving comfort and safety, and increasing the noise when vehicles pass. In severe cases, the speed of vehicles passing is greatly reduced, and additional impact loads are placed on the road surface and bridges, affecting the service life of the bridges. Therefore, once the road surface height difference occurs, reasonable and scientific prevention and control measures need to be taken to deal with it.
[0003] At present, hot material repair, cement repair, cold material repair and other repair methods are generally used for typical height difference diseases in bridge expansion joints, around pit covers and uneven settlement of bridge heads. Hot material has strong bonding performance with the original road surface and good effect. However, hot material repair is usually suitable for large-scale construction, and the cost of local repair is high, and it is easy to cause problems in mixing, paving, construction organization and other links. Cement repair materials have outstanding strength and durability, but there are disadvantages such as long construction and maintenance cycle and poor bonding with the original road surface. Cold material repair is convenient to construct and has a wide range of application scenarios. However, the material itself has durability problems such as weak bonding with the old road surface interface and poor resistance to water damage. In addition, once the height difference disease site is formed, the stress-strain response is complex under the action of vehicle load. The application of traditional repair materials is prone to secondary damage and the height difference disease will reappear, making it difficult to restore the flatness of the road surface and ensure driving safety. Therefore, there is an urgent need for a new height difference repair material that is convenient to construct, has good bonding with the original road surface, has strong coordinated deformation ability and excellent durability.
[0004] In order to solve the above problems, the new generation of road traffic construction has begun to adopt a new type of pavement material and construction method - semi-flexible pavement material. Semi-flexible pavement materials have the characteristics of both cement and asphalt, and can synergistically play the advantages of cement's high rigidity and strong bearing capacity and asphalt's good flexibility and strong load transfer capacity. Therefore, the application and development prospects of semi-flexible pavement materials are broad. However, among semi-flexible pavement materials, asphalt is oleophilic, and there is a repulsive effect between asphalt and cement mortar. When used for road height difference repair, the compatibility between cement slurry and asphalt slurry is poor, thereby reducing the compressive strength of the road surface and resulting in poor volume stability of the road surface. Summary of the invention
[0005] The present application provides a semi-flexible road height difference repair material and a preparation method and application thereof, in order to solve the above-mentioned problems mentioned in the background technology.
[0006] On the one hand, the present application provides a semi-flexible pavement height difference repair material, which includes cement-based dry powder mortar, SBR-SiO2 composite modified emulsified asphalt mixture, aggregate and water in a mass ratio of 1000: (40-140): (800-1000): (110-130) respectively;
[0007] The cement-based dry-mix mortar comprises, by weight: 350-400 parts by weight of rapid-hardening sulphoaluminate cement, 20-40 parts by weight of ordinary Portland cement, 15-30 parts by weight of silica fume, 20-35 parts by weight of gypsum, 1-10 parts by weight of fly ash, 520-580 parts by weight of quartz sand, 10-20 parts by weight of rubber powder, 2-4 parts by weight of water reducing agent, 0.0-1.0 parts by weight of lithium carbonate, 0.2-3 parts by weight of boric acid, 0.35-0.85 parts by weight of water-absorbing resin, 0.5-1.0 parts by weight of defoaming agent, 0.3-1.5 parts by weight of water retaining agent and 0.1-0.8 parts by weight of expansion agent;
[0008] The SBR-SiO2 composite modified emulsified asphalt mixture comprises: 124-170 parts by weight of SBR-SiO2 composite modified emulsified asphalt, 1-5 parts by weight of carbon nanofibers, 1-5 parts by weight of carbon nanotubes and 0.2-0.4 parts by weight of potassium methyl silicate;
[0009] SBR-SiO2 composite modified emulsified asphalt is obtained by modifying base asphalt with SBR and nano-SiO2.
[0010] Nano-SiO2 increases the compatibility between substances, improves the bonding ability between SBR and asphalt interface, and improves the performance of emulsified asphalt; while carbon nanofibers and nano-silica improve the relative dynamic modulus of the material, reduce the microcracks inside the material, and reduce the mass loss rate after freezing and thawing, thereby improving frost resistance and enhancing durability.
[0011] The water reducing agent is a powdered polycarboxylic acid water reducing agent, which has excellent water reducing rate, fluidity, and permeability, and can also enhance the strength of cement mortar. The defoamer destroys the surface tension of the bubbles and makes the bubbles dissipate quickly, thereby reducing the voids in the repair material and improving the compactness and strength of the repaired road surface. The defoamer can be any suitable defoamer, preferably, an organosilicon defoamer, such as dimethyl silicone oil and methyl silicone oil. The water retaining agent can improve the fluidity and plasticity of concrete, making it easier to process and shape, thereby improving the construction efficiency during repair. Preferably, the water retaining agent selects cellulose ether. The swelling agent produces expanded crystals through hydration, compensates for the shrinkage of cement during hydration, prevents material cracks, and can also enhance the waterproof performance of the repair material structure. The swelling agent is preferably selected from calcium sulfoaluminate swelling agents, such as alum stone swelling agent and CSA swelling agent.
[0012] Optionally, the rapid hardening sulphoaluminate cement is R.SAC42.5 or R.SAC52.5, and the ordinary Portland cement is PO42.5 or PO52.5.
[0013] Optionally, the aggregate is selected from at least one of limestone, sandstone and granite.
[0014] Optionally, the particle size classification of the aggregate is 0-3mm, 3-5mm, 5-10mm, 10-15mm; and the aggregate is selected from one or more of the above particle size classifications.
[0015] Optionally, the rubber powder is at least one of ethylene-vinyl acetate copolymer rubber powder, acrylic polymer rubber powder, polyethylene oxide rubber powder, styrene-acrylic rubber powder, and styrene-butadiene rubber powder.
[0016] Optionally, the particle size of quartz sand is classified into 10-20 mesh, 20-40 mesh, 40-70 mesh, and 70-140 mesh, wherein the weight of quartz sand of 10-20 mesh is 385-387 parts, the weight of quartz sand of 20-40 mesh is 100-106 parts, the weight of quartz sand of 40-70 mesh is 60-65 parts, and the weight of quartz sand of 70-140 mesh is 49-52 parts.
[0017] On the other hand, the present application provides a method for preparing a semi-flexible pavement height difference repair material, the preparation method is used to prepare the above-mentioned semi-flexible pavement height difference repair material, the preparation method comprises:
[0018] (1) Preparation of SBR-SiO2 composite modified emulsified asphalt mixture:
[0019] (101) Preparation of emulsified asphalt: heating the base asphalt to 140-150°C to obtain hot melt asphalt, adding an emulsifier aqueous solution and a stabilizer to the hot melt asphalt, and mechanically dispersing the mixture to obtain emulsified asphalt;
[0020] (102) Preparation of SBR modified emulsified asphalt: SBR was added to emulsified asphalt, the temperature was maintained at 140-150°C, and the mixture was stirred at a speed of 5000-5500 r / min for 10-15 min to obtain SBR modified emulsified asphalt;
[0021] (103) Preparation of SBR-SiO2 composite modified emulsified asphalt: Add nano-silicon dioxide to SBR modified emulsified asphalt, maintain the temperature at 140-150°C, and stir at a speed of 5000-5500 r / min for 10-15 min to obtain SBR-SiO2 composite modified emulsified asphalt;
[0022] (104) Mixture preparation: Add carbon nanofibers, carbon nanotubes and potassium methyl silicate to SBR-SiO2 composite modified emulsified asphalt, maintain the temperature at 140-150° C., and stir at a speed of 5000-5500 r / min for 10-15 min to prepare an SBR-SiO2 composite modified emulsified asphalt mixture;
[0023] (2) Preparation of cement-based dry-mix mortar: Add quick-hardening sulphoaluminate cement, ordinary Portland cement, silica fume, gypsum, fly ash, quartz sand, rubber powder, water reducer, lithium carbonate, boric acid, water-absorbing resin, defoamer, water-retaining agent and expansion agent into a container according to weight parts, and stir and mix at a speed of 150-200 r / min for 15-20 min to obtain cement-based dry-mix mortar, which is then sealed in a moisture-proof packaging bag.
[0024] (3) Preparation of semi-flexible pavement height difference repair material: Add cement-based dry powder mortar into a mixer according to weight, stir at a speed of 60-70 r / min for 45-60 s, then add water and SBR-SiO2 composite modified emulsified asphalt mixture, stir at a speed of 150-200 r / min for 120 s, finally add aggregate, stir at a speed of 200-1000 r / min for 3-10 min, and obtain semi-flexible pavement height difference repair material.
[0025] Optionally, the amount of base asphalt is 100 parts by weight, the amount of emulsifier aqueous solution is 20-60 parts by weight, the amount of stabilizer is 2-10 parts by weight, the amount of SBR is 2-5 parts by weight, and the amount of nano-silica is 2-5 parts by weight.
[0026] Optionally, in the emulsified asphalt preparation step, the mass concentration of the emulsifier in the emulsifier aqueous solution is 1%-30%, and the emulsifier is selected from an anionic emulsifier or a cationic emulsifier.
[0027] On the other hand, the present application provides an application of a semi-flexible pavement height difference repair material in repairing the height difference of a road or bridge surface. The height difference repair material is the above-mentioned semi-flexible pavement height difference repair material, or the height difference repair material prepared by the above-mentioned method.
[0028] The semi-flexible road height difference repair material and its preparation method and application provided in the present application realize the preparation and application of the road height difference repair material, and have the following beneficial effects compared with the prior art:
[0029] (1) The present application combines the characteristics of both cement and asphalt, and can synergistically bring into play the advantages of cement's high rigidity and strong bearing capacity and asphalt's good flexibility and strong load transfer capacity. The semi-flexible and semi-rigid characteristics of the repair material provided by the present application not only effectively solve the problem of repairing high-difference road surfaces, but also improve the compatibility between asphalt materials and cement materials, and have good bonding properties with old road surfaces. It also makes the repaired road surface have strong compressive strength and volume stability, improves the road surface's anti-rutting ability, reduces the bumps and vibrations during vehicle driving, improves driving comfort and safety, and greatly improves the durability of the road surface. In addition, the present application has no toxic gas emissions through the repair material, which is safe and environmentally friendly. At the same time, room temperature mixing also has the advantages of energy saving and high efficiency. It is easy to mix during construction, simple to operate, has good bonding properties with old road surfaces, does not require heating throughout the process, protects the environment and reduces the cost of road surface materials. It is suitable for road surface high-difference repairs on highways of all grades.
[0030] (2) First, the base asphalt is heated and melted to obtain hot melt asphalt. SBR is added to modify the base asphalt to obtain SBR modified emulsified asphalt, and then nano silicon dioxide is added to further modify it to obtain SBR-SiO2 composite modified emulsified asphalt. Finally, carbon nanofibers, carbon nanotubes and potassium methyl silicate are added to obtain SBR-SiO2 composite modified emulsified asphalt mixture. In the preparation step of cement-based dry powder mortar, the required components are first stirred and mixed according to weight parts to obtain cement-based dry powder mortar, and sealed in a moisture-proof packaging bag to avoid moisture in the air from entering and cement agglomeration. When in use, the cement-based dry powder mortar is added to a mixer and stirred at a speed of 60-70r / min for 45-60s. The cement-based dry powder mortar is first broken up to facilitate uniform mixing with subsequent components. Water and SBR-SiO2 composite modified emulsified asphalt mixture are then added, stirred, and finally aggregate is added to obtain a semi-flexible road height difference repair material. Nano-SiO2 increases the compatibility between substances, improves the bonding ability between SBR and asphalt interface, and improves the performance of emulsified asphalt; while carbon nanofibers and nano-silica improve the relative dynamic modulus of the material, reduce the microcracks inside the material, and reduce the mass loss rate after freezing and thawing, thereby improving frost resistance and enhancing durability.
[0031] (3) The height difference repair material provided in this application is suitable for repairing height differences in roads of all grades, and has no toxic gas emissions, is safe and environmentally friendly. At the same time, when the height difference repair material is used for repairing height difference roads, it only needs to be mixed at room temperature, and has the advantages of energy saving and high efficiency. It is easy to mix during construction, simple to operate, and has good bonding performance with the old road surface. No heating is required throughout the process, which protects the environment and reduces the cost of road materials. At the same time, the traffic time is open for 2 hours. DETAILED DESCRIPTION
[0032] In order to make the purpose, technical scheme and advantages of the embodiments of the present application clearer, the technical scheme in the embodiments of the present application is clearly and completely described below. Obviously, the described embodiments are part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without creative work also fall within the scope of protection of the present application.
[0033] On the one hand, the present application provides a semi-flexible pavement height difference repair material, which includes cement-based dry powder mortar, SBR-SiO2 composite modified emulsified asphalt mixture, aggregate and water in a mass ratio of 1000: (40-140): (800-1000): (110-130) respectively;
[0034] The cement-based dry-mix mortar comprises, by weight: 350-400 parts by weight of rapid-hardening sulphoaluminate cement, 20-40 parts by weight of ordinary Portland cement, 15-30 parts by weight of silica fume, 20-35 parts by weight of gypsum, 1-10 parts by weight of fly ash, 520-580 parts by weight of quartz sand, 10-20 parts by weight of rubber powder, 2-4 parts by weight of water reducing agent, 0.0-1.0 parts by weight of lithium carbonate, 0.2-3 parts by weight of boric acid, 0.35-0.85 parts by weight of water-absorbing resin, 0.5-1.0 parts by weight of defoaming agent, 0.3-1.5 parts by weight of water retaining agent and 0.1-0.8 parts by weight of expansion agent;
[0035] The SBR-SiO2 composite modified emulsified asphalt mixture comprises: 124-170 parts by weight of SBR-SiO2 composite modified emulsified asphalt, 1-5 parts by weight of carbon nanofibers, 1-5 parts by weight of carbon nanotubes and 0.2-0.4 parts by weight of potassium methyl silicate;
[0036] SBR-SiO2 composite modified emulsified asphalt is obtained by modifying base asphalt with SBR and nano-SiO2.
[0037] Specifically, the repair material provided by the present application includes cement-based dry-powder mortar, SBR-SiO2 composite modified emulsified asphalt mixture, aggregate and water. The cement-based dry-powder mortar provides a gelling effect, and can form a slurry after adding water and stirring. This slurry can harden in the air or water, so that the components in the repair material are firmly bonded together to form a strong whole, which not only makes the repair material have good strength and density, but also can improve the durability of the repair material. Emulsified asphalt can form a nearly seamless waterproof layer on the repair surface, effectively preventing water penetration and erosion, thereby extending the service life of the road surface, and at the same time can fill the pores of the cement structure, enhance the bearing capacity and strength of the cement-based dry-powder mortar, and improve the crack resistance. The SBR-SiO2 composite modified emulsified asphalt mixture provided in the present application is obtained by emulsifying the base asphalt and then modifying it with SBR and nano-SiO2. SBR is a copolymer of butadiene and styrene and has a porous structure. It can absorb small molecular components and oil in asphalt. At the same time, SBR contains some light components. When the repair material is laid on the uneven road surface, the light components are slowly released into the asphalt, thereby enhancing the deformation ability of the asphalt at low temperatures. The deformation of the asphalt can absorb a large part of the energy released by the freezing and expansion of free water, thereby improving the frost resistance of the emulsified asphalt mortar.
[0038] Since asphalt is a high molecular polymer with strong hydrophobicity, its bonding performance and compatibility with cement-based mortar are weak, which reduces the compressive strength of the road surface and causes poor volume stability of the road surface. Nano silicon dioxide increases the compatibility between substances, improves the binding ability of SBR and asphalt interface, improves the compatibility of emulsified asphalt and cement mortar, improves the uniformity of the repair material, thereby improving the density of the internal structure of the repair material and enhancing the compressive strength. The present application also improves the compatibility between cement-based mortar and emulsified asphalt material by adding carbon nanofibers and carbon nanotubes. The incorporation of carbon nanofibers can significantly improve the relative dynamic elastic modulus of emulsified asphalt mortar and reduce the mass loss rate. Carbon nanofibers overlap each other in asphalt to form a good network structure. When stress is transmitted from the cement mortar matrix to the emulsified asphalt, carbon nanofibers can play a role of connection and transmission, and absorb most of the stress, so that the stress is released, and the appearance of cracks is prevented, so the compressive strength of the repair material is significantly improved. Carbon nanotubes can transform the thin hexagonal plate-like calcium hydroxide crystals at the interface between cement-based mortar and asphalt into hexagonal prism-like crystals, increasing the compactness of the interface, and the carbon nanotubes that penetrate the asphalt and cement paste also increase the bonding performance of the interface. The strengthening of the interface between cement paste and asphalt reduces the defects inside the cement asphalt mortar and improves the synergistic deformation performance between the two, which is conducive to enhancing the deformation resistance of cement emulsified asphalt mortar and the volume stability of the pavement. It can also improve the compatibility and adhesion of the repair material with the base material, improve the compressive strength and durability of the repair material, and at the same time, the carbon nanotubes dispersed in the asphalt can hinder the free movement of the asphalt polymer chain segments, and to a certain extent improve the deformation resistance of the repair material. In the presence of cement-based dry powder mortar, carbon nanofibers and carbon nanotubes can react with Ca(OH)2 to generate more CSH gel, occupy the void space, and increase the density of the interface transition zone. Therefore, incorporating two types of nanoparticles, carbon nanofibers and carbon nanotubes, into emulsified asphalt will help produce more cement hydrates, which can absorb the free asphalt therein, thereby also helping to improve the compatibility between asphalt and cement and increase the compressive strength of the repair material.
[0039] Rapid hardening sulphoaluminate cement, ordinary Portland cement and silica fume in cement-based dry mortar provide early strength of the repair material. Rapid hardening sulphoaluminate cement and ordinary Portland cement mainly play the role of forming cement stone gel, bonding other components together to form a whole, thus improving the strength of the repair material. At the same time, the two cements can form a good spatial structure with other components, providing excellent durability. The specific surface area of silica fume is 20000m 2 / kg, which helps to make the components compatible and mixed, and helps to build a denser and stronger spatial structure between the components, thereby improving the compressive strength and durability of the repair material and improving the volume stability of the road surface.
[0040] Gypsum can delay the setting time of the repair material. Gypsum and potassium methyl silicate work together to improve the hardness and density of the repair material. Potassium methyl silicate has a hydrophobic effect, which reduces the contact range between gypsum particles and water and reduces the SO4 dissolved by gypsum. 2- ion concentration, thereby reducing the SO4 2- The influence of excessive ions on the hydration process of C3A in cement. At the same time, the dihydrate gypsum crystals of gypsum dissolution and recrystallization are reduced, making the internal structure of the semi-flexible repair material more compact, thereby improving the compressive strength of the road surface and significantly improving the mechanical properties. Among them, potassium methyl silicate uses an aqueous solution with a solid content of 40wt%.
[0041] At the same time, the composite action of lithium carbonate and boric acid and the synergistic effect of cement form a ternary system, which further improves the durability of the repair material.
[0042] The present application combines the characteristics of both cement and asphalt, and can synergistically play the advantages of cement's high rigidity and strong bearing capacity and asphalt's good flexibility and strong load transfer capacity. The semi-flexible and semi-rigid characteristics of the repair material provided by the present application not only effectively solve the repair of the height difference road surface, improve the compatibility between the asphalt material and the cement material, and have good bonding performance with the old road surface, but also make the repaired road surface have strong compressive strength and volume stability, improve the road surface's anti-rutting ability, reduce the bumps and vibrations during vehicle driving, improve driving comfort and safety, and greatly improve the durability of the road surface. In addition, the present application has no toxic gas discharge through the repair material, which is safe and environmentally friendly. At the same time, room temperature mixing also has the advantages of energy saving and high efficiency, easy mixing during construction, simple operation, good bonding performance with the old road surface, no need to heat the whole process, protect the environment and reduce the cost of road surface materials, and is suitable for road height difference repairs on highways of all grades.
[0043] Optionally, the rapid hardening sulphoaluminate cement is R.SAC42.5 or R.SAC52.5, and the ordinary Portland cement is PO42.5 or PO52.5.
[0044] Specifically, fast-hardening sulphoaluminate cement has the characteristics of rapid solidification, which reduces the time of opening traffic and minimizes the impact on traffic, thereby simplifying the process and reducing production costs. And fast-hardening sulphoaluminate cement concrete can still maintain high strength and frost resistance at low temperatures. Ordinary Portland cement can tightly bond the various components together to form a concrete structure with a certain strength, but it has a long solidification time and its early strength is lower than that of fast-hardening sulphoaluminate cement. By mixing fast-hardening sulphoaluminate cement and ordinary Portland cement, the solidification time of the repair material is reduced, and the early strength of the repair material can also be enhanced, thereby improving the compressive strength of the repair material.
[0045] At the same time, the combination of the two cements in special weight portions improves the mixing uniformity of the cement-based dry-mixed mortar and the composite modified emulsified asphalt mixture. The SBR-SiO2 composite modified emulsified asphalt mixture can better enter the gaps in the cement-based dry-mixed mortar, making the spatial structure of the repair material tighter, thereby improving the compressive strength of the repair material.
[0046] Optionally, the aggregate is selected from at least one of limestone, sandstone and granite.
[0047] Optionally, the particle size classification of the aggregate is 0-3mm, 3-5mm, 5-10mm, 10-15mm; and the aggregate is selected from one or more of the above particle size classifications.
[0048] Specifically, aggregates can increase the strength and rigidity of the repair material and reduce the shrinkage and expansion of concrete. After the aggregates are mixed with cement-based dry mortar, a solid hardening system is formed, thereby improving the compressive strength and tensile strength of the repair material, and increasing the bearing capacity and durability of the repair material.
[0049] Factors such as the size, shape, surface characteristics, and coarseness of the aggregate will directly affect the plasticity and moldability of the repair material. For example, larger aggregates can increase the protrusions formed by concrete on the concrete surface, thereby increasing the anti-skid property of the concrete, while smaller aggregates can increase the compactness and looseness of the concrete. Aggregates can also reduce the permeability of the repair material, preventing the infiltration of moisture and air molecules in the repair material, thereby increasing the durability of the road surface. In the repair material of this application, any one or more aggregates of particle size classification can be selected (such as 3-5mm aggregates or a combination with 0-3mm aggregates when the height difference is ≤2cm, 5-10mm aggregates or a combination with 0-3mm aggregates when the height difference is 2-5cm are preferably used, and 10-15mm aggregates or a combination with 0-3mm aggregates and 3-5mm aggregates are preferably used when the height difference is greater than 5cm), and the specifications of JTG 3420-2020 "Test Procedures for Cement and Cement Concrete for Highway Engineering" can be achieved according to the actual working conditions, and are not particularly limited here. Among them, 0mm in 0-3mm aggregate means no aggregate is used.
[0050] Optionally, the rubber powder is at least one of ethylene-vinyl acetate copolymer rubber powder, acrylic polymer rubber powder, polyethylene oxide rubber powder, styrene-acrylic rubber powder, and styrene-butadiene rubber powder. The rubber powder can improve the toughness of the repair material.
[0051] Optionally, the particle size of quartz sand is classified into 10-20 mesh, 20-40 mesh, 40-70 mesh, and 70-140 mesh, wherein the weight of quartz sand of 10-20 mesh is 385-387 parts, the weight of quartz sand of 20-40 mesh is 100-106 parts, the weight of quartz sand of 40-70 mesh is 60-65 parts, and the weight of quartz sand of 70-140 mesh is 49-52 parts.
[0052] Specifically, quartz sand can increase the compressive strength of the repair material, reduce shrinkage cracks, increase durability and improve working performance. By adding quartz sand of different particle sizes in a graded manner, it can help fill the voids in the concrete, increase the density of the repair material, and thus reduce the occurrence of shrinkage cracks. At the same time, quartz sand has high hardness and good durability, which can reduce the aging speed of the repair material and extend the service life of the road surface.
[0053] Preferably, the SBR-SiO2 composite modified emulsified asphalt mixture also includes 0.15-0.26 parts by weight of kojic acid, 0.3-0.85 parts by weight of methyl butynol and 0.56-1.5 parts by weight of potassium cinnamate. When the repair material is laid, the hydroxyl group of kojic acid and the carboxyl group on potassium cinnamate easily react with the active group on the nano-silicon dioxide, so that the six-membered heterocyclic ring contained in kojic acid and the benzene ring at the other end of the potassium cinnamate structure can also be grafted on the surface of the nano-silicon dioxide. The silicon dioxide modifies the emulsified asphalt, which not only further disperses the kojic acid and potassium cinnamate in the repair material with the emulsified asphalt, but also the six-membered heterocyclic ring and the benzene ring can improve the mechanical strength of the repair material, thereby improving the compressive strength and durability of the repair material. Methylbutynol can form bonds with the active groups of carbon nanofibers and carbon nanotubes, improve the dispersibility and stability of carbon nanofibers and carbon nanotubes, and then improve the reaction of carbon nanofibers and carbon nanotubes with Ca(OH)2, generate more CSH gel, occupy the void space, and increase the density of the interface transition zone. Produce more cement hydrates, which also helps to improve the compatibility between asphalt and cement and improve the compressive strength of the repair material. The three work together to further improve the compressive strength of the repair material.
[0054] On the other hand, the present application provides a method for preparing a semi-flexible pavement height difference repair material, the preparation method is used to prepare the above-mentioned semi-flexible pavement height difference repair material, the preparation method comprises:
[0055] (1) Preparation of SBR-SiO2 composite modified emulsified asphalt mixture:
[0056] (101) Preparation of emulsified asphalt: heating the base asphalt to 140-150°C to obtain hot melt asphalt, adding an emulsifier aqueous solution and a stabilizer to the hot melt asphalt, and mechanically dispersing for 10-15 minutes to obtain emulsified asphalt;
[0057] (102) Preparation of SBR modified emulsified asphalt: SBR was added to emulsified asphalt, the temperature was maintained at 140-150°C, and the mixture was stirred at a speed of 5000-5500 r / min for 10-15 min to obtain SBR modified emulsified asphalt;
[0058] (103) Preparation of SBR-SiO2 composite modified emulsified asphalt: Add nano-silicon dioxide to SBR modified emulsified asphalt, maintain the temperature at 140-150°C, and stir at a speed of 5000-5500 r / min for 10-15 min to obtain SBR-SiO2 composite modified emulsified asphalt;
[0059] (104) Mixture preparation: Add carbon nanofibers, carbon nanotubes and potassium methyl silicate to SBR-SiO2 composite modified emulsified asphalt, maintain the temperature at 140-150° C., and stir at a speed of 5000-5500 r / min for 10-15 min to prepare an SBR-SiO2 composite modified emulsified asphalt mixture;
[0060] (2) Preparation of cement-based dry-mix mortar: Add quick-hardening sulphoaluminate cement, ordinary Portland cement, silica fume, gypsum, fly ash, quartz sand, rubber powder, water reducer, lithium carbonate, boric acid, water-absorbing resin, defoamer, water-retaining agent and expansion agent into a container according to weight parts, and stir and mix at a speed of 150-200 r / min for 15-20 min to obtain cement-based dry-mix mortar, which is then sealed in a moisture-proof packaging bag.
[0061] (3) Preparation of semi-flexible pavement height difference repair material: Add cement-based dry powder mortar into a mixer according to weight, stir at a speed of 60-70 r / min for 45-60 s, then add water and SBR-SiO2 composite modified emulsified asphalt mixture, stir at a speed of 150-200 r / min for 120 s, finally add aggregate, stir at a speed of 200-1000 r / min for 3-10 min, and obtain a semi-flexible pavement height difference repair material.
[0062] The present application realizes the preparation of semi-flexible road height difference repair material through the above scheme. First, the base asphalt is heated to 140-150°C to melt the asphalt to obtain hot-melt asphalt. Then SBR is added to modify the base asphalt to obtain SBR modified emulsified asphalt, and then nano-silicon dioxide is added for further modification to obtain SBR-SiO2 composite modified emulsified asphalt. Finally, carbon nanofibers, carbon nanotubes and potassium methyl silicate are added to obtain SBR-SiO2 composite modified emulsified asphalt mixture.
[0063] In the preparation step of cement-based dry mortar, the required components are first stirred and mixed according to weight to obtain cement-based dry mortar, and then sealed in a moisture-proof packaging bag to prevent moisture from entering the air and prevent cement from caking. When in use, the cement-based dry mortar is added to a mixer and stirred at a speed of 60-70r / min for 45-60s. The cement-based dry mortar is first broken up to facilitate uniform mixing with subsequent components. Then water and SBR-SiO2 composite modified emulsified asphalt mixture are added, stirred, and finally aggregate is added to obtain a semi-flexible pavement height difference repair material.
[0064] Among them, the SBR binding rate is 23.5%, the solid content is 64%, the pH value is 6, the Brookfield viscosity is 500-1500, and the particle charge is positive. The carbon nanofiber length is 10-30um, the diameter is 160-200nm, and the specific surface area is 2000m 2 / g.
[0065] Optionally, the amount of base asphalt is 100 parts by weight, the amount of emulsifier aqueous solution is 20-60 parts by weight, the amount of stabilizer is 2-10 parts by weight, the amount of SBR is 2-5 parts by weight, and the amount of nano-silica is 2-5 parts by weight.
[0066] Specifically, the matrix asphalt adopts any commonly used matrix asphalt in the industry, preferably, common 70# matrix asphalt is adopted. Emulsifier is used to emulsify the matrix asphalt, which helps SBR and SiO2 to modify the matrix asphalt. Stabilizer helps to maintain the stability of emulsified asphalt when emulsifying the matrix asphalt, and is conducive to maintaining the uniform suspension of the solution during subsequent modification, improving the stability of SBR-SiO2 composite modified emulsified asphalt mixture, improving the stability of the repair material, helping the repair material to play a role to the greatest extent when repairing the height difference road surface, and improving the compressive strength and durability of the road surface. Preferably, stabilizer adopts calcium chloride or magnesium chloride.
[0067] Optionally, in the emulsified asphalt preparation step, the mass concentration of the emulsifier in the emulsifier aqueous solution is 1%-30%, and the emulsifier is selected from an anionic emulsifier or a cationic emulsifier.
[0068] Specifically, the emulsifier can effectively inhibit the agglomeration of particles and reduce cohesion, thereby increasing the fluidity of the repair material, which makes it easier for the repair material to flow and fill during construction. More preferably, the emulsifier is sodium dodecylbenzene sulfonate.
[0069] On the other hand, the present application also provides an application of a semi-flexible pavement height difference repair material in repairing the height difference of a road or bridge surface. The height difference repair material is the above-mentioned semi-flexible pavement height difference repair material, or the height difference repair material prepared by the above-mentioned method.
[0070] Specifically, the height difference repair material provided in the present application is suitable for repairing height differences in roads of all grades, and has no toxic gas emissions, is safe and environmentally friendly. At the same time, when the height difference repair material is used for repairing height difference roads, it only needs to be mixed at room temperature, and has the advantages of energy saving and high efficiency. It is easy to mix during construction, easy to operate, has good adhesion to the old road surface, does not require heating throughout the process, protects the environment and reduces the cost of road materials, and is open to traffic for 2 hours.
[0071] It should be noted that, in the present invention and the following embodiments, concentrations, ratios, etc. not otherwise specified are all weight concentrations, weight ratios, etc., "%" means weight percentage, and "parts" means parts by weight, which are common writing habits used by those skilled in the art and are therefore not described in detail in the present invention.
[0072] The present invention is further described in detail below in conjunction with the examples. However, it should be understood that the examples are for illustrative purposes only and are not intended to limit the scope of the present invention.
[0073] Example 1
[0074] Preparation of SBR-SiO2 composite modified emulsified asphalt mixture:
[0075] (101) Preparation of emulsified asphalt: 100 parts by weight of base asphalt is heated to 145° C. to obtain hot melt asphalt, 40 parts by weight of an emulsifier aqueous solution and 6 parts by weight of a stabilizer are added to the hot melt asphalt, and mechanical dispersion is performed to obtain emulsified asphalt;
[0076] (102) Preparation of SBR modified emulsified asphalt: 3 parts by weight of SBR was added to emulsified asphalt, the temperature was maintained at 145°C, and the mixture was stirred at a speed of 5000-5500 r / min for 15 min to obtain SBR modified emulsified asphalt;
[0077] (103) Preparation of SBR-SiO2 composite modified emulsified asphalt: 3 parts by weight of nano-silicon dioxide was added to SBR modified emulsified asphalt, the temperature was maintained at 145°C, and the mixture was stirred at a speed of 5000-5500 r / min for 15 min to obtain SBR-SiO2 composite modified emulsified asphalt;
[0078] (104) Preparation of mixture: To 140 parts by weight of SBR-SiO2 composite modified emulsified asphalt, 3 parts by weight of carbon nanofibers, 3 parts by weight of carbon nanotubes, 0.3 parts by weight of potassium methyl silicate, 0.2 parts by weight of kojic acid, 0.4 parts by weight of methyl butynol and 0.8 parts by weight of potassium cinnamate were added. The mixture was stirred at 5000-5500 r / min for 15 min while maintaining the temperature at 145°C to obtain an SBR-SiO2 composite modified emulsified asphalt mixture.
[0079] Comparative Example 1
[0080] Preparation of SBR-SiO2 composite modified emulsified asphalt mixture:
[0081] The difference from Example 1 is that:
[0082] (104) Preparation of mixture: To 140 parts by weight of SBR-SiO2 composite modified emulsified asphalt, 3 parts by weight of carbon nanofibers, 3 parts by weight of carbon nanotubes, 0.3 parts by weight of potassium methyl silicate, 0.4 parts by weight of methyl butynol and 0.8 parts by weight of potassium cinnamate were added. The mixture was stirred at 5000-5500 r / min for 15 min while maintaining the temperature at 145°C to obtain an SBR-SiO2 composite modified emulsified asphalt mixture.
[0083] Comparative Example 2
[0084] Preparation of SBR-SiO2 composite modified emulsified asphalt mixture:
[0085] The difference from Example 1 is that:
[0086] (104) Preparation of mixture: To 140 parts by weight of SBR-SiO2 composite modified emulsified asphalt, 3 parts by weight of carbon nanofibers, 3 parts by weight of carbon nanotubes, 0.3 parts by weight of potassium methyl silicate, 0.2 parts by weight of kojic acid, and 0.8 parts by weight of potassium cinnamate were added. The mixture was stirred at 5000-5500 r / min for 15 min while maintaining the temperature at 145°C to obtain an SBR-SiO2 composite modified emulsified asphalt mixture.
[0087] Comparative Example 3
[0088] Preparation of SBR-SiO2 composite modified emulsified asphalt mixture:
[0089] The difference from Example 1 is that:
[0090] (104) Preparation of mixture: To 140 parts by weight of SBR-SiO2 composite modified emulsified asphalt, 3 parts by weight of carbon nanofibers, 3 parts by weight of carbon nanotubes, 0.3 parts by weight of potassium methyl silicate, 0.2 parts by weight of kojic acid, and 0.4 parts by weight of methyl butynol were added. The mixture was stirred at 5000-5500 r / min for 15 min while maintaining the temperature at 145°C to obtain an SBR-SiO2 composite modified emulsified asphalt mixture.
[0091] Experimental Example 1
[0092] Referring to JTGF40-2011 "Technical Specifications for Highway Asphalt Pavement Construction", the performance of SBR-SiO2 composite modified emulsified asphalt mixture was tested. Three parallel tests were set up for each test group, and the average value was taken. The test results and specific test methods are shown in Table 1:
[0093] Table 1
[0094]
[0095]
[0096] As shown in Table 1, the SBR-SiO2 composite modified emulsified asphalt mixture can be successfully prepared by the technical method provided by the present application, and all indicators meet or even exceed the values specified in the Technical Specifications for Highway Asphalt Pavement Construction. Among them, the hydroxyl group of kojic acid and the carboxyl group on potassium cinnamate easily react with the active groups on nano-silica, so that the six-membered heterocyclic ring contained in kojic acid and the benzene ring at the other end of the potassium cinnamate structure can also be grafted on the surface of nano-silica, and the silicon dioxide modifies the emulsified asphalt, so that the kojic acid and potassium cinnamate are further dispersed in the repair material with the emulsified asphalt, and the methylbutynol can form a bond with the active groups of carbon nanofibers and carbon nanotubes, thereby improving the dispersibility and stability of carbon nanofibers and carbon nanotubes, improving the storage stability of asphalt, and thus improving the stability of the repair material.
[0097] Example 2
[0098] A method for preparing a semi-flexible pavement height difference repair material comprises the following steps:
[0099] (1) Preparation of SBR-SiO2 composite modified emulsified asphalt mixture:
[0100] (101) Preparation of emulsified asphalt: 100 parts by weight of base asphalt was heated to 140° C. to obtain hot melt asphalt, 20 parts by weight of an emulsifier aqueous solution and 2 parts by weight of a stabilizer were added to the hot melt asphalt, and mechanical dispersion was performed for 10 minutes to obtain emulsified asphalt;
[0101] (102) Preparation of SBR modified emulsified asphalt: 2 parts by weight of SBR was added to emulsified asphalt, the temperature was maintained at 140°C, and the mixture was stirred at a speed of 5000-5500 r / min for 10 min to obtain SBR modified emulsified asphalt;
[0102] (103) Preparation of SBR-SiO2 composite modified emulsified asphalt: Add 2 parts by weight of nano-silicon dioxide to SBR modified emulsified asphalt, maintain the temperature at 140°C, and stir at a speed of 5000-5500 r / min for 10 min to obtain SBR-SiO2 composite modified emulsified asphalt;
[0103] (104) Mixture preparation: Add 1 part by weight of carbon nanofiber, 1 part by weight of carbon nanotube, and 0.2 part by weight of potassium methyl silicate to 124 parts by weight of SBR-SiO2 composite modified emulsified asphalt, maintain the temperature at 140°C, and stir at a speed of 5000-5500 r / min for 10 min to obtain an SBR-SiO2 composite modified emulsified asphalt mixture;
[0104] (2) Preparation of cement-based dry-mix mortar: 350 parts by weight of rapid-hardening sulphoaluminate cement, 20 parts by weight of ordinary Portland cement, 15 parts by weight of silica fume, 20 parts by weight of gypsum, 1 part by weight of fly ash, 520 parts by weight of quartz sand (385 parts by weight of 10-20 mesh quartz sand, 100 parts by weight of 20-40 mesh quartz sand, 60 parts by weight of 40-70 mesh quartz sand, and 70- 49 parts by weight of 140-mesh quartz sand), 10 parts by weight of glue powder, 2 parts by weight of water reducing agent, 0.2 parts by weight of boric acid, 0.35 parts by weight of water-absorbing resin, 0.5 parts by weight of defoaming agent, 0.3 parts by weight of water retaining agent and 0.1 parts by weight of expansion agent are added into a container, and stirred and mixed at a speed of 150-200r / min for 15 minutes to obtain cement-based dry mortar, which is then sealed in a moisture-proof packaging bag.
[0105] The rapid hardening sulphoaluminate cement is R.SAC42.5, and the ordinary Portland cement is PO42.5.
[0106] (3) Preparation of semi-flexible pavement height difference repair material: Add cement-based dry powder mortar into a mixer according to weight, stir at a speed of 60-70 r / min for 45-60 s, then add water and SBR-SiO2 composite modified emulsified asphalt mixture, stir at a speed of 150-200 r / min for 120 s, finally add aggregate, stir at a speed of 200-1000 r / min for 3-10 min, and obtain semi-flexible pavement height difference repair material.
[0107] The mass ratios of cement-based dry-mixed mortar, SBR-SiO2 composite modified emulsified asphalt mixture, aggregate and water are 1000:40:800:110 respectively, and the aggregate is selected from 5-10 mm limestone.
[0108] Example 3
[0109] A method for preparing a semi-flexible pavement height difference repair material comprises the following steps:
[0110] (1) Preparation of SBR-SiO2 composite modified emulsified asphalt mixture:
[0111] (101) Preparation of emulsified asphalt: 100 parts by weight of base asphalt was heated to 145° C. to obtain hot melt asphalt, 40 parts by weight of an emulsifier aqueous solution and 6 parts by weight of a stabilizer were added to the hot melt asphalt, and mechanical dispersion was performed for 12 minutes to obtain emulsified asphalt;
[0112] (102) Preparation of SBR modified emulsified asphalt: 3 parts by weight of SBR was added to emulsified asphalt, the temperature was maintained at 145°C, and the mixture was stirred at a speed of 5000-5500 r / min for 12 min to obtain SBR modified emulsified asphalt;
[0113] (103) Preparation of SBR-SiO2 composite modified emulsified asphalt: Add 3 parts by weight of nano-silicon dioxide to SBR modified emulsified asphalt, maintain the temperature at 145°C, and stir at a speed of 5000-5500 r / min for 12 min to obtain SBR-SiO2 composite modified emulsified asphalt;
[0114] (104) Mixture preparation: Add 3 parts by weight of carbon nanofibers, 3 parts by weight of carbon nanotubes, and 0.3 parts by weight of potassium methyl silicate to 150 parts by weight of SBR-SiO2 composite modified emulsified asphalt, maintain the temperature at 145°C, and stir at a speed of 5000-5500 r / min for 12 min to obtain an SBR-SiO2 composite modified emulsified asphalt mixture;
[0115] (2) Preparation of cement-based dry-mix mortar: 380 parts by weight of rapid-hardening sulphoaluminate cement, 30 parts by weight of ordinary Portland cement, 25 parts by weight of silica fume, 25 parts by weight of gypsum, 6 parts by weight of fly ash, 550 parts by weight of quartz sand (386 parts by weight of 10-20 mesh quartz sand, 103 parts by weight of 20-40 mesh quartz sand, 62 parts by weight of 40-70 mesh quartz sand, 70-140 mesh quartz sand, 100 parts by weight of ... 50 parts by weight of quartz sand), 15 parts by weight of glue powder, 3 parts by weight of water reducing agent, 0.6 parts by weight of lithium carbonate, 2.2 parts by weight of boric acid, 0.55 parts by weight of water-absorbing resin, 0.7 parts by weight of defoaming agent, 1.2 parts by weight of water retaining agent and 0.5 parts by weight of expansion agent are added into a container, and stirred and mixed at a speed of 150-200r / min for 12 minutes to obtain cement-based dry mortar, which is then sealed in a moisture-proof packaging bag.
[0116] The rapid hardening sulphoaluminate cement is R.SAC42.5, and the ordinary Portland cement is PO42.5.
[0117] (3) Preparation of semi-flexible pavement height difference repair material: Add cement-based dry powder mortar into a mixer according to weight, stir at a speed of 60-70 r / min for 45-60 s, then add water and SBR-SiO2 composite modified emulsified asphalt mixture, stir at a speed of 150-200 r / min for 120 s, finally add aggregate, stir at a speed of 200-1000 r / min for 3-10 min, and obtain semi-flexible pavement height difference repair material.
[0118] The mass ratios of cement-based dry-mixed mortar, SBR-SiO2 composite modified emulsified asphalt mixture, aggregate and water are 1000:90:900:120 respectively, and the aggregate is selected from 5-10 mm limestone.
[0119] Example 4
[0120] A method for preparing a semi-flexible pavement height difference repair material comprises the following steps:
[0121] (1) Preparation of SBR-SiO2 composite modified emulsified asphalt mixture:
[0122] (101) Preparation of emulsified asphalt: 100 parts by weight of base asphalt was heated to 150° C. to obtain hot melt asphalt, 60 parts by weight of an emulsifier aqueous solution and 10 parts by weight of a stabilizer were added to the hot melt asphalt, and mechanical dispersion was performed for 15 minutes to obtain emulsified asphalt;
[0123] (102) Preparation of SBR modified emulsified asphalt: 5 parts by weight of SBR was added to emulsified asphalt, the temperature was maintained at 150°C, and the mixture was stirred at a speed of 5000-5500 r / min for 15 min to obtain SBR modified emulsified asphalt;
[0124] (103) Preparation of SBR-SiO2 composite modified emulsified asphalt: Add 5 parts by weight of nano-silicon dioxide to SBR modified emulsified asphalt, maintain the temperature at 150°C, and stir at a speed of 5000-5500 r / min for 15 min to obtain SBR-SiO2 composite modified emulsified asphalt;
[0125] (104) Mixture preparation: 5 parts by weight of carbon nanofibers, 5 parts by weight of carbon nanotubes, and 0.4 parts by weight of potassium methyl silicate were added to 170 parts by weight of SBR-SiO2 composite modified emulsified asphalt, the mixture was stirred at 5000-5500 r / min for 15 min while maintaining the temperature at 150°C to obtain an SBR-SiO2 composite modified emulsified asphalt mixture;
[0126] (2) Preparation of cement-based dry-mix mortar: 400 parts by weight of rapid-hardening sulphoaluminate cement, 40 parts by weight of ordinary Portland cement, 30 parts by weight of silica fume, 35 parts by weight of gypsum, 10 parts by weight of fly ash, 580 parts by weight of quartz sand (387 parts by weight of 10-20 mesh quartz sand, 106 parts by weight of 20-40 mesh quartz sand, 65 parts by weight of 40-70 mesh quartz sand, and 70-140 mesh quartz sand) were mixed into a mortar. 52 parts by weight of quartz sand), 20 parts by weight of glue powder, 4 parts by weight of water reducing agent, 1.0 parts by weight of lithium carbonate, 3 parts by weight of boric acid, 0.85 parts by weight of water-absorbing resin, 1.0 parts by weight of defoaming agent, 1.5 parts by weight of water retaining agent and 0.8 parts by weight of expansion agent are added into a container, and stirred and mixed at a speed of 150-200r / min for 20 minutes to obtain cement-based dry mortar, which is sealed in a moisture-proof packaging bag.
[0127] The rapid hardening sulphoaluminate cement is R.SAC42.5, and the ordinary Portland cement is PO42.5.
[0128] (3) Preparation of semi-flexible pavement height difference repair material: Add cement-based dry powder mortar into a mixer according to weight, stir at a speed of 60-70 r / min for 45-60 s, then add water and SBR-SiO2 composite modified emulsified asphalt mixture, stir at a speed of 150-200 r / min for 120 s, finally add aggregate, stir at a speed of 200-1000 r / min for 3-10 min, and obtain semi-flexible pavement height difference repair material.
[0129] The mass ratios of cement-based dry-mixed mortar, SBR-SiO2 composite modified emulsified asphalt mixture, aggregate and water are 1000:140:1000:130 respectively, and the aggregate is selected from 3-5 mm limestone.
[0130] Comparative Example 5
[0131] A method for preparing a semi-flexible pavement height difference repair material comprises the following steps:
[0132] The difference from Example 3 is that:
[0133] (1) Preparation of SBR-SiO2 composite modified emulsified asphalt mixture:
[0134] (104) Mixture preparation: 0.4 parts by weight of potassium methyl silicate was added to 170 parts by weight of SBR-SiO2 composite modified emulsified asphalt, the temperature was maintained at 150°C, and the mixture was stirred at a speed of 5000-5500 r / min for 15 min to obtain an SBR-SiO2 composite modified emulsified asphalt mixture.
[0135] Experimental Example 2
[0136] Referring to JTG 3420-2020 "Testing Procedures for Cement and Cement Concrete in Highway Engineering", the performance of the semi-flexible pavement height difference repair materials provided in Examples 2 to 4 and Comparative Example 5 was tested, and 3 parallel tests were set for each test group, and the average value was taken. The test results are shown in Table 2:
[0137] Table 2
[0138]
[0139]
[0140] It can be seen from Table 2 that the semi-flexible pavement height difference repair material provided by the present application has good compressive strength, and the compressive strength after 2 hours of maintenance reaches more than 23MPa, which meets the regulations for opening to traffic, greatly shortens the pavement repair time, and reduces the impact of the repair process on traffic. It also has good flexural strength and dynamic elastic modulus, and adds carbon nanofibers and carbon nanotubes to improve the compatibility between cement-based mortar and emulsified asphalt. The incorporation of carbon nanofibers can significantly increase the relative dynamic elastic modulus of emulsified asphalt mortar and reduce the mass loss rate. The carbon nanofibers overlap each other in the asphalt to form a good network structure. When stress is transmitted from the cement mortar matrix to the emulsified asphalt, the carbon nanofibers can play a role in connection and transmission, and absorb most of the stress, so that the stress is released and the appearance of cracks is prevented, thereby significantly improving the compressive strength of the repair material.
[0141] At the same time, the cyclic frost resistance of the repair material provided by the present application is much higher than that of Comparative Example 4. Asphalt in the emulsified asphalt mortar is a viscoelastic material, and its modulus is much lower than that of cement. During the freezing and thawing process, the free water inside the emulsified asphalt mortar freezes and expands. Due to the good deformation performance of asphalt, part of the energy can be absorbed to prevent the emulsified asphalt mortar from frost heave damage. Carbon nanofibers and carbon nanotubes are dispersed in the emulsified asphalt. The two nanomaterials overlap each other in the emulsified asphalt to form a good network structure. When stress is transmitted from the cement mortar matrix to the emulsified asphalt, the carbon nanofibers and carbon nanotubes can absorb most of the stress, so that the stress is released and the appearance of cracks in the emulsified asphalt mortar is prevented, thereby significantly improving the frost resistance of the emulsified asphalt mortar.
[0142] Example 5
[0143] A method for preparing a semi-flexible pavement height difference repair material comprises the following steps:
[0144] The difference from Example 3 is that:
[0145] (104) Preparation of mixture: To 150 parts by weight of SBR-SiO2 composite modified emulsified asphalt, 3 parts by weight of carbon nanofibers, 3 parts by weight of carbon nanotubes, 0.3 parts by weight of potassium methyl silicate, 0.15 parts by weight of kojic acid, 0.3 parts by weight of methyl butynol and 0.56 parts by weight of potassium cinnamate were added. The mixture was stirred at 5000-5500 r / min for 12 min while maintaining the temperature at 145°C to obtain an SBR-SiO2 composite modified emulsified asphalt mixture.
[0146] Example 6
[0147] A method for preparing a semi-flexible pavement height difference repair material comprises the following steps:
[0148] The difference from Example 3 is that:
[0149] (104) Preparation of mixture: To 150 parts by weight of SBR-SiO2 composite modified emulsified asphalt, 3 parts by weight of carbon nanofibers, 3 parts by weight of carbon nanotubes, 0.3 parts by weight of potassium methyl silicate, 0.2 parts by weight of kojic acid, 0.55 parts by weight of methyl butynol and 1.0 parts by weight of potassium cinnamate were added. The mixture was stirred at 5000-5500 r / min for 12 min while maintaining the temperature at 145°C to obtain an SBR-SiO2 composite modified emulsified asphalt mixture.
[0150] Example 7
[0151] A method for preparing a semi-flexible pavement height difference repair material comprises the following steps:
[0152] The difference from Example 3 is that:
[0153] (104) Preparation of mixture: To 150 parts by weight of SBR-SiO2 composite modified emulsified asphalt, 3 parts by weight of carbon nanofibers, 3 parts by weight of carbon nanotubes, 0.3 parts by weight of potassium methyl silicate, 0.26 parts by weight of kojic acid, 0.85 parts by weight of methyl butynol and 1.5 parts by weight of potassium cinnamate were added. The mixture was stirred at 5000-5500 r / min for 12 min while maintaining the temperature at 145°C to obtain an SBR-SiO2 composite modified emulsified asphalt mixture.
[0154] Comparative Example 6
[0155] The difference from Example 6 is that:
[0156] (104) Mixture preparation: 3 parts by weight of carbon nanofibers, 3 parts by weight of carbon nanotubes, 0.3 parts by weight of potassium methyl silicate, 0.85 parts by weight of methyl butynol and 1.5 parts by weight of potassium cinnamate were added to 150 parts by weight of SBR-SiO2 composite modified emulsified asphalt, the mixture was stirred at 5000-5500 r / min for 12 min while maintaining the temperature at 145°C to obtain an SBR-SiO2 composite modified emulsified asphalt mixture. Comparative Example 8
[0157] The difference from Example 6 is that:
[0158] (104) Preparation of mixture: To 150 parts by weight of SBR-SiO2 composite modified emulsified asphalt, 3 parts by weight of carbon nanofibers, 3 parts by weight of carbon nanotubes, 0.3 parts by weight of potassium methyl silicate, 0.26 parts by weight of kojic acid and 1.5 parts by weight of potassium cinnamate were added. The mixture was stirred at 5000-5500 r / min for 12 min while maintaining the temperature at 145°C to obtain an SBR-SiO2 composite modified emulsified asphalt mixture.
[0159] Comparative Example 7
[0160] The difference from Example 6 is that:
[0161] (104) Preparation of mixture: To 150 parts by weight of SBR-SiO2 composite modified emulsified asphalt, add 3 parts by weight of carbon nanofibers, 3 parts by weight of carbon nanotubes, 0.3 parts by weight of potassium methyl silicate, 0.26 parts by weight of kojic acid, and 0.85 parts by weight of methyl butynol. Maintain the temperature at 145°C and stir at a speed of 5000-5500 r / min for 12 min to obtain an SBR-SiO2 composite modified emulsified asphalt mixture.
[0162] Experimental Example 3
[0163] Semi-flexible pavement height difference repair materials were successfully prepared by Examples 5 to 7. Taking Example 6 as an example, referring to JTG 3420-2020 "Test Procedures for Cement and Cement Concrete in Highway Engineering", the compressive strength of the repair materials obtained from Comparative Examples 6 to 8 was tested. Three parallel tests were set up for each test group, and the average value was taken. The test results are shown in Table 3:
[0164] Table 3
[0165]
[0166] The results show that the addition of kojic acid, methylbutynol and potassium cinnamate to the repair material significantly improves the compressive strength of the repair material. This is because when repairing the road surface, the cement-based dry powder mortar, aggregate and SBR-SiO2 composite modified emulsified asphalt in the repair material synergistically play the advantages of cement rigidity and strong bearing capacity and asphalt flexibility and strong load transfer capacity, providing the main carrier for the repair material, and the hydroxyl group of kojic acid and the carboxyl group on potassium cinnamate easily react with the active groups on nano-silica, which not only further makes kojic acid and potassium cinnamate dispersed in the repair material with emulsified asphalt, but also the six-membered heterocyclic ring and benzene ring can improve the mechanical strength of the repair material, thereby improving the compressive strength and durability of the repair material. Methylbutynol can form bonds with the active groups of carbon nanofibers and carbon nanotubes, improve the dispersibility and stability of carbon nanofibers and carbon nanotubes, and then improve the reaction of carbon nanofibers and carbon nanotubes with Ca(OH)2, generate more CSH gel, occupy the void space, and increase the density of the interface transition zone. Producing more cement hydrates can also help improve the compatibility between asphalt and cement and increase the compressive strength of the repair material. The three factors work together to further improve the compressive strength of the repair material.
[0167] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present application, rather than to limit it. Although the present application has been described in detail with reference to the aforementioned embodiments, ordinary technicians in the field should understand that they can still modify the technical solutions recorded in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present application.
Claims
1. A semi-flexible road height difference repair material, characterized in that: The repair material comprises cement-based dry powder mortar, SBR-SiO2 composite modified emulsified asphalt mixture, aggregate and water in a mass ratio of 1000: (40-140): (800-1000): (110-130) respectively; The cement-based dry-mix mortar comprises, by weight: 350-400 parts of rapid-hardening sulphoaluminate cement, 20-40 parts of ordinary Portland cement, 15-30 parts of silica fume, 20-35 parts of gypsum, 1-10 parts of fly ash, 520-580 parts of quartz sand, 10-20 parts of rubber powder, 2-4 parts of water reducing agent, 0.0-1.0 parts of lithium carbonate, 0.2-3 parts of boric acid, 0.35-0.85 parts of water-absorbing resin, 0.5-1.0 parts of defoaming agent, 0.3-1.5 parts of water-retaining agent and 0.1-0.8 parts of expansion agent; The SBR-SiO2 composite modified emulsified asphalt mixture comprises: 124-170 parts by weight of SBR-SiO2 composite modified emulsified asphalt, 1-5 parts by weight of carbon nanofibers, 1-5 parts by weight of carbon nanotubes and 0.2-0.4 parts by weight of potassium methyl silicate; The SBR-SiO2 composite modified emulsified asphalt is obtained by modifying base asphalt with SBR and nano-SiO2.
2. The semi-flexible pavement height difference repair material according to claim 1, characterized in that: The rapid hardening sulphoaluminate cement is R.SAC42.5 or R.SAC52.5, and the ordinary Portland cement is PO42.5 or PO52.
5.
3. The semi-flexible pavement height difference repair material according to claim 1, characterized in that: The aggregate is selected from at least one of limestone, sandstone and granite.
4. The semi-flexible pavement height difference repair material according to claim 3, characterized in that: The aggregate has a particle size classification of 0-3 mm, 3-5 mm, 5-10 mm, and 10-15 mm; and the aggregate is selected from one or more of the above particle size classifications.
5. The semi-flexible pavement height difference repair material according to claim 1, characterized in that: The rubber powder is at least one of ethylene-vinyl acetate copolymer rubber powder, acrylic polymer rubber powder, polyethylene oxide rubber powder, styrene-acrylic rubber powder and styrene-butadiene rubber powder.
6. The semi-flexible pavement height difference repair material according to claim 5, characterized in that: The particle size of the quartz sand is classified into 10-20 mesh, 20-40 mesh, 40-70 mesh, and 70-140 mesh, wherein the weight portion of the quartz sand of 10-20 mesh is 385-387 parts, the weight portion of the quartz sand of 20-40 mesh is 100-106 parts, the weight portion of the quartz sand of 40-70 mesh is 60-65 parts, and the weight portion of the quartz sand of 70-140 mesh is 49-52 parts.
7. A method for preparing a semi-flexible pavement height difference repair material, characterized in that: The preparation method is used to prepare the semi-flexible pavement height difference repair material as described in any one of claims 1 to 6 above, and the preparation method comprises: (1) Preparation of SBR-SiO2 composite modified emulsified asphalt mixture: (101) Preparation of emulsified asphalt: heating the base asphalt to 140-150° C. to obtain hot melt asphalt, adding an emulsifier aqueous solution and a stabilizer to the hot melt asphalt, and performing mechanical dispersion to obtain the emulsified asphalt; (102) Preparation of SBR modified emulsified asphalt: adding SBR to the emulsified asphalt, maintaining the temperature at 140-150° C., stirring at a speed of 5000-5500 r / min for 10-15 min, to obtain the SBR modified emulsified asphalt; (103) Preparation of SBR-SiO2 composite modified emulsified asphalt: adding nano-silicon dioxide to the SBR modified emulsified asphalt, maintaining the temperature at 140-150° C., stirring at a speed of 5000-5500 r / min for 10-15 min, to obtain the SBR-SiO2 composite modified emulsified asphalt; (104) Mixture preparation: adding carbon nanofibers, carbon nanotubes and potassium methyl silicate to the SBR-SiO2 composite modified emulsified asphalt, maintaining the temperature at 140-150° C., and stirring at a speed of 5000-5500 r / min for 10-15 min to obtain the SBR-SiO2 composite modified emulsified asphalt mixture; (2) Preparation of cement-based dry-mix mortar: Add the rapid-hardening sulphoaluminate cement, the ordinary Portland cement, the silica fume, the gypsum, the fly ash, the quartz sand, the rubber powder, the water reducer, the lithium carbonate, the boric acid, the water-absorbing resin, the defoamer, the water-retaining agent and the expansion agent into a container according to weight parts, and stir and mix at a speed of 150-200 r / min for 15-20 minutes to obtain the cement-based dry-mix mortar, which is then sealed in a moisture-proof packaging bag; (3) Preparation of semi-flexible pavement height difference repair material: Add the cement-based dry powder mortar into a mixer according to weight, stir at a speed of 60-70 r / min for 45-60 s, then add the water and the SBR-SiO2 composite modified emulsified asphalt mixture, stir at a speed of 150-200 r / min for 120 s, finally add the aggregate, stir at a speed of 200-1000 r / min for 3-10 min, and obtain the semi-flexible pavement height difference repair material.
8. The method for preparing the semi-flexible pavement height difference repair material according to claim 7, characterized in that: The amount of the base asphalt is 100 parts by weight, the amount of the emulsifier aqueous solution is 20-60 parts by weight, the amount of the stabilizer is 2-10 parts by weight, the amount of the SBR is 2-5 parts by weight, and the amount of the nano-silicon dioxide is 2-5 parts by weight.
9. The method for preparing the semi-flexible pavement height difference repair material according to claim 8, characterized in that: In the emulsified asphalt preparation step, the mass concentration of the emulsifier in the emulsifier aqueous solution is 1%-30%, and the emulsifier is selected from anionic emulsifiers or cationic emulsifiers.
10. Application of a semi-flexible road height difference repair material in road and bridge deck height difference repair, characterized in that: The height difference repair material is the semi-flexible pavement height difference repair material as described in any one of claims 1 to 6, or the height difference repair material prepared by the method as described in any one of claims 7 to 9.
Citation Information
Patent Citations
Asphalt base composite material for pavement crack repair
CN103613333A
Composite cold repair material for asphalt pavement pit repair
CN103951344A
Nanoparticle SBR (styrene butadiene rubber) composite modified asphalt and preparation method thereof
CN104277463A
Emulsified asphalt modified by carbon nanometer fiber and preparing method thereof
CN105315684A
Asphalt concrete pavement pit slot rapid remedy material and preparation method thereof
CN117800690A